New directions in e-learning research in health professions education: report of two symposia - Triola, Marc M.; Huwendiek, Sören (Medical teacher, 2012)
Background: The use of Computer Assisted Instruction (CAI) is rising across health professions education. Research to date is of limited use in guiding the implementation and selection of CAI innovations. Aims: In the context of two symposia, systemic reviews were discussed that evaluate literature in Internet-based learning, Virtual Patients, and animations. Each session included a debate with the goal of reaching consensus on best current practices and future research. Methods: Thematic analysis of the discussions was performed to arrange the questions by theme, eliminate redundancy, and craft them into a cohesive narrative. Results: The question analysis revealed that there are clear advantages to the use of CAI, and that established educational theories should certainly inform the future development and selection of CAI tools. Schools adopting CAI need to carefully consider the benefits, cost, available resources, and capacity for teachers and learners to accept change in their practice of education. Potential areas for future research should focus on the effectiveness of CAI instructional features, integration of e-learning into existing curricula and with other modalities like simulation, and the use of CAI in assessment of higher-level outcomes. Conclusions: There are numerous opportunities for future research and it will be important to achieve consensus on important themes.